Dating experience, shyness and physical attractiveness in Croatian females: Age differences - Zarevski, Predrag (Array, 1996)
Adolescence is the most critical period of our lives considering dating and development of shyness. The goal of this study was to establish prevalence and interrelationships among shyness, self-rated physical attractiveness and dating experience in Croatian female high-school graduates (N = 518) and university students (N = 387). Subjects were asked to report the number of longer and more stable romantic relationships they had with the opposite sex, to rate their physical attractiveness on a seven point numerical scale and to complete the Shyness scale. Results indicate that shyness is higher in high-school graduates than in university sudents and that shyer females have less dating experience than unshy ones. No age difference in self-rated physical attractiveness was found. In the subsample of high school graduates the self-rated shyness proved to be a stronger predictor for dating experience than attractiveness. For the university students both predictors are of the sampe importance for dating behavior.